THE NEXUS BETWEEN FDI, EXTERNAL (IM)BALANCE AND ECONOMIC GROWTH ON SERBIAN REAL CONVERGENCE PATH - Sekulić, Aleksandar; Beker Pucar, Emilija; Glavaški, Olgica (The European Journal of Applied Economics, 2024)
The focus of this research is the nexus between FDIs, external imbalance and economic growth, in the case of Serbia in the period 2007-2024. From one side, convergence process towards more developed European economies implies fostering of economic growth i.e. real convergence, which is positively connected with FDIs inflows. From the other side, real convergence is usually accompanied with growing external imbalance i.e. current account deficit. The aim of this research is to shed more light into these relations from the angle of national economy, under methodological framework of estimated VAR model. Empirical findings confirm that FDIs positively influence real convergence, while real convergence is connected with external imbalance deterioration. National economic authorities should continue efforts to maintain and attract FDIs as beneficial type of external capital inflows, having in mind their positive real repercussions and medium-term external balancing. Nevertheless, essential and long-run efforts should be oriented towards resolving of chronic CA deficit, thereby increasing country’s resistance to global crisis shocks and sudden stop episodes.